Influence of Backbone Curvature on the Organic Electrochemical Transistor Performance of Glycolated Donor–Acceptor Conjugated Polymers. (6th August 2021) - Ding, Bowen; Kim, Gunwoo; Kim, Youngseok; Eisner, Flurin D.; Gutiérrez‐Fernández, Edgar; Martín, Jaime; Yoon, Myung‐Han; Heeney, Martin
Abstract: Two new glycolated semiconducting polymers PgBT(F)2gT and PgBT(F)2gTT of differing backbone curvatures were designed and synthesised for application as p‐type accumulation mode organic electrochemical transistor (OECT) materials. Both polymers demonstrated stable and reversible oxidation, accessible within the aqueous electrochemical window, to generate polaronic charge carriers. OECTs fabricated from PgBT(F)2gT featuring a curved backbone geometry attained a higher volumetric capacitance of 170 F cm −3 . However, PgBT(F)2gTT with a linear backbone displayed overall superior OECT performance with a normalised peak transconductance of 3.00×10 4 mS cm −1, owing to its enhanced order, expediting the charge mobility to 0.931 cm 2 V −1 s −1 . Abstract : The targeted design of backbone geometries is shown to influence the p‐type accumulation mode organic electrochemical transistor (OECT) performance of two glycolated donor–acceptor conjugated polymers, PgBT(F)2gT and PgBT(F)2gTT .